Two-colour photocurrent detection technique for coherent control of a single InGaAs/GaAs quantum dot - Boyle, Stephen J.; Ramsay, Andrew J.; Kolodka, Roman S.; Oliveira, José Brás Barreto de [UNESP]; Liu, Hui Yun; Hopkinson, Mark; Fox, A. Mark; Skolnick, Maurice S. (Wiley-Blackwell, 2009)
We present a two-colour photocurrent detection method for coherent control of a single InGaAs/GaAs self-assembled quantum dot. A pulse shaping technique provides a high degree of control over picosecond optical pulses. Rabi rotations on the exciton to biexciton transition are presented, and fine structure beating is detected via time-resolved measurements. (c) 2009 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim